ZAIN-UL-ABIDIN’S REGIN: A GOLDEN ERA OF PEACE, PROSPERITY AND PROGRESS IN KASHMIR - Sarfaraz Ahmad Rather; Shabir Ahmad Dar; Muneer Ahmad Dar (RADJA PUBLIKA, 2023)
Zain-ul-Abidin, also known as Bud Shah, was a notable king of Kashmir who ushered in a period of peace, prosperity, and benevolent rule for nearly half a century. He was a liberal ruler who established peace in his kingdom and promoted the welfare of his subjects. During his reign, Muslim rule firmly established its roots in Kashmir, and he became the harbinger of new thoughts and ideas. He encouraged the arts, literature, and music, and his court was a hub of culture and creativity. Zain-ul-Abidin was deeply committed to the development of Kashmir and took great interest in the developmental programs in all aspects of life. He undertook tours to different parts of the country to find out the condition of the people and how his officers were carrying out the administration. Zain-ul-Abidin's legacy is still remembered in Kashmir today, and he is revered as one of the greatest kings of the region. Hence an attempt has been made in this research article to trace the social, cultural and political development of the region during the period of Sultan Zain ul Abidin.